ETHICS AND GOVERNANCE OF AI IN HEALTHCARE: CASE INDONESIA, EU, AND THE US - Mochamad Kevin Romadhona; Rachmat Dimas Oktafenanda (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2025)
Artificial Intelligence (AI) is rapidly transforming healthcare systems globally, offering unprecedented opportunities for diagnostics, personalized treatment, and health management. However, its deployment raises complex ethical and governance challenges, particularly concerning privacy, fairness, accountability, and equitable access. This study examines the ethics and governance of AI in healthcare through a comparative lens, focusing on Indonesia, the European Union (EU), and the United States (US). The study employs a qualitative comparative methodology, combining policy analysis, legal review, and literature synthesis. National laws, regulatory frameworks, ethical guidelines, and institutional practices were systematically examined to identify normative foundations, regulatory mechanisms, and institutional capacities. Key challenges and emerging best practices were analyzed to understand the position of Indonesia within the global AI governance landscape. Findings indicate that the EU prioritizes a rights-based, precautionary approach with enforceable legal frameworks and strong institutional oversight, emphasizing privacy, fairness, and trustworthiness. The US promotes an innovation-driven, decentralized model, relying on sector-specific regulation and voluntary ethical frameworks, which allows rapid technological adoption but creates regulatory fragmentation and health equity concerns. Indonesia exhibits an intermediate position, adopting global ethical norms through the Personal Data Protection Law and Digital Health Blueprint, yet facing enforcement, oversight, and capacity constraints. The study concludes that Indonesia can benefit from a hybrid governance approach, combining EU-style enforceable ethical standards with US-style adaptive regulatory mechanisms and innovation incentives. Policy recommendations include strengthening legal and ethical frameworks, implementing risk-based oversight, building institutional and technical capacity, promoting equity, and fostering public–private partnerships. Aligning domestic AI governance with international best practices will enable Indonesia to harness AI’s potential in healthcare while safeguarding ethical standards and public trust.